Hubungan antara Perubahan Suhu Udara Harian, Perilaku Petani dan Keankeragaman Serangga Penyerbuk di Desa Serang Kecamatan Karangreja, Kabupaten Purbalingga Jawa Tengah (The relationship between the Air Temperature Change Daily, Farmer Behavior, and Diver - Dwi YULIANI; Moh. Husein SASTRANEGARA (Universitas Jambi, 2015)
Global warming has threatened Indonesian’s agricultural sector and put the sectorvulnerable to climate change. The changes affect the daily air temperature changes, farmerbehavior, and the diversity of insect pollinators. The study aims to determine the daily changes inair temperature, farmer behavior, and diversity of pollinating insects in the village of Serang,Karangreja, Purbalingga, Central Java; and to analyze the relationship between daily airtemperature changes, farmer behavior, and insect pollinators diversity. The research employedsurvey methods. Samples for the daily air temperature measurement were taken purposeviley. Thediversity of insect pollinators on the three farming type and respondens were selected radmonlywith total respondent 99. The results showed that the average daily air temperature in chili farms ishigher than that in tomato and strawberry farm; farmers have a good knowledge about theenvironmental degradation of agriculture land, good attitude and awareness in maintaining andimproving the quality of agriculture, but they have negative behaviour in the use of excessiveinsecticides. Species richness of insect pollinators in tomato farm is higher than that in chili andstrawberry farm. A good knowledge, good attitude, and bad behaviour are closely related to thedaily air temperature and insect pollinators.